Pengaruh Kontrol Diri Dan Efikasi Diri Terhadap Prokrastinasi Akademik Dalam Menyelesaikan Skripsi Mahasiswa Program Studi Pendidikan Ekonomi STKIP PGRI Tulungagung - Khusnawatul Mudalifah; Novi Ilham Madhuri (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
A thesis is an obligation for students who take the last semester in private and public universities as the final assignment to get a bachelor's degree. When the condition of students is not good it will lead to the tendency of academic procrastination to students. So that self-control and self-efficacy will influence the occurrence of academic procrastination. The method of data collection in this study uses quantitative research methods with a population of 114 students. The sampling technique was done by simple random sampling using the Solvin formula with 53 samples. The results of the research show several things. First, the value of t-count (-4,289)> t table (2,009) and there is a significant negative effect of self-control on student academic procrastination partially. Second, the value of t-count (-5,200)> t-table (2,009) and there is a significant negative effect on the partial self-efficacy of student academic procrastination. Third, the value of F-count (18,968) > F-table (3,18) and there is a significant influence between self-control and self-efficacy towards academic procrastination in completing the thesis on Semester Economic Education Study Program students VIII STKIP PGRI Tulungagung Year 2018/2019.